Prevalence of ectoparasites in betta fish (Betta splendens R.) in Pekalongan City - Linayati - Linayati; Tri - Yusufi Mardiana; Ishadiyanto Ishadiyanto; Muhammad Zulkham Yahya (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2022)
ABSTRACT In Pekalongan City, Betta fish, or Siamese fighting fish is gaining popularity. However, many problems often occur in Betta fish care, such as disease attacks from parasites, including ectoparasites. This research identified the types of ectoparasites in Betta fish and determined its prevalence and degree of infection in betta fish in Pekalongan City. In this exploratory research, data were descriptively analyzed. The data were obtained from 60 samples of betta fish measuring 3.5–5.6 cm taken from betta farmers in Pekalongan City. The results of this research revealed that Tetrahymena sp and Ichthyopthirius multifilis had different prevalence levels of 46.66% for that 3.5 – 4.5 cm in length, and 43.33% of fish with 4.6-5.6 cm long, respectively 44,6 % and 40 % for Ichtyoptirius multifilis. The infection value was 6.79/fish for Tetrahymena sp (moderate), and 4.6/fish for Ichthyopthirius multifilis (low). The water quality parameters were; the temperature of 27.1 – 28.90C, DO 5.8 – 8.2 mg/l, and a pH of 6.3 – 7.3.Keywords: Ectoparasite, Betta Fish, Prevalence, Tetrahymena